A Stimulation and rehabilitation program: Oficina da Lembrança - Rodrigo Krug; Lariane Ono; Anna Quialheiro; Eleonora d’Orsi; Luiz Ramos; André Xavier (Revista Brasileira de Atividade Física e Saúde)
This study aimed to present the method of the multi-center program of cognitive stimulation and rehabilitation known as  “Oficina da Lembrança” (Memory Workshop), held at the University of Southern Santa Catarina, Federal University of Santa Catarina and Federal University of São Paulo. This project has assisted about 450 people aged 50 or older with memory complaints. Each session consists of one to three meetings/week (approximately 20 meetings/semester), with groups of 10 to 20 participants to carry out activities on computers, physical activity and individual oral reports of the experiences they had at the meetings (approximately 90 minutes). In the first and final six-monthly meeting, socio-demographic, health and behavioral variables, cognitive performance, functional disability and presence of depressive symptoms are collected. The project was implemented in 2006 and it is expected to continue. Programs like this are extremely important in society because they can provide benefits to the population, especially in terms of helping cognitive improvement, thus promoting health and socialization.